Education on Exposure and Health Risks of Forever Chemicals (PFAS) for Housewives and Adolescent Girls - Ilmiawati, Cimi; Silvia, Roza; Arisanty, Dessy; Usman, Elly; Masrul; Amir, Arni; Hasmiwati; Reza, Mohamad; Ariadapa Rahadi, Didan; Fauzan, Rezky; Abi Ghofari Siregar, Muhammad; Olivia, Ivonne; Dwiharyani, Yuli; Ilham, Muhammad (Warta Pengabdian Andalas, 2026)
Our community service activity aimed to increase knowledge and awareness about the dangers of per- and polyfluoroalkyl substances (PFAS), known as “forever chemicals,” which are commonly found in household products, food packaging, and cosmetics. Long-term exposure to PFAS has been associated with numerous serious health effects, including an increased risk of several cancers, disruption of hormone homeostasis, liver toxicity, impaired immune function, and adverse reproductive and developmental outcomes.  The participants included housewives and adolescent girls (n = 20) who attended Padang Pasir Community Health Center, East Padang, Padang on 6 September 2025. An interactive educational session was conducted using a pre-test–post-test design to evaluate changes in knowledge and awareness. Analysis of participants who completed both assessments showed an improvement in knowledge following the intervention, with the greatest increases observed in understanding of healthy cooking utensils (50%) and the presence of persistent chemicals in cosmetics (50%). However, evaluation of awareness levels revealed only a minimal increase in median scores (from 57 to 60), which was not statistically significant (p = 0.221). We conclude that a focused educational session is effective in improving participants’ cognitive knowledge, but a more comprehensive and sustained approach is needed to promote meaningful behavioral change and deeper awareness, particularly since practicality and convenience remain major considerations when choosing household products, food packaging, and cosmetics.